Identifikasi dan Analisis Faktor Penyebab Dispensing Error pada Pelayanan Resep di Klinik Esti Husada Kota Semarang - Lia Nur Asdiyati Rahma; Eleonora Maryeta Toy; Karol Giovani Battista Leki (PT Bukuloka Literasi Bangsa, 2025)
This study aims to analyze the description of dispensing errors and their causes in the prescription service process at the Esti Husada Clinic in Semarang City as an effort to improve patient safety and the quality of pharmaceutical services. The study used a mixed method design with a sequential explanatory approach, combining quantitative and qualitative methods. The quantitative stage was conducted through non-experimental descriptive prospective observation of 330 BPJS patient prescriptions during the period of May–July 2025 using an observation sheet in the form of a checklist compiled based on pharmaceutical service standards. The qualitative stage was conducted through semi-structured interviews with pharmaceutical personnel to identify the factors causing the errors. Quantitative data were analyzed descriptively using frequency distribution and percentages, while qualitative data were analyzed using thematic analysis. The results showed that out of 330 prescriptions observed, there were 2 dispensing errors (0.6%), namely errors in the stage of preparing drugs that did not match the prescription request, while other stages such as compounding, labeling, rechecking, drug delivery, and providing information to patients were found to be error-free. Qualitative findings showed that workload, work experience, communication, and the educational level of pharmacy personnel were factors that could potentially influence the occurrence of dispensing errors. Overall, the low error rate indicates that pharmaceutical services at the clinic have been running quite well, but continuous prevention efforts are still needed through workload management, improving the competence of pharmaceutical personnel, and strengthening the re-examination system to maintain patient safety. Keywords: dispensing error, pharmaceutical services, patient safety, drug prescriptions, clinics.